The complete mitochondrial genome of Pseudobagrus pratti and its phylogeny - Yuanchao Zou; Meng Xie; Cheng Tang; Xin Li; Peng Fu; Junying Zhang; Xinbin Duan (Mitochondrial DNA. Part B. Resources, 2019)
Pseudobagrus pratti is a unique freshwater fish and mainly distributed in the Yangtze River and Pearl River systems. In this study, the complete mitochondrial genome of P. pratti was first determined. The total length of the complete mitochondrial genome is 16,533 bp, contained 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, one D-loop locus, and an origin of replication on the light-strand (OL). The overall nucleotide composition was 31.55% A, 26.76% T, 26.78% C, 14.91% G, with 58.31% AT, respectively. Phylogenetic analysis both highly supported that P. pratti showed a close relationship with P. ussuriensis and P. emarginatus. These data would contribute to elucidate the evolutionary mechanisms and biogeography of Pseudobagrus and is useful for the conservation of genetics and stock evaluation for P. pratti.